Contrast-Induced Nephropathy in Renal Transplant Recipients: A Single Center Experience - Abu Jawdeh, Bassam G.; Leonard, Anthony C.; Sharma, Yuvraj; Katipally, Swapna; Shields, Adele R.; Alloway, Rita R.; Woodle, E. Steve; Thakar, Charuhas V. (Frontiers in Medicine, 2017)
Background: Contrast-induced nephropathy (CIN) in native kidneys is associated with a significant increase in mortality and morbidity. Data regarding CIN in renal allografts is limited however. We retrospectively studied CIN in renal allografts at our institution: its incidence, risk factors and effect on long-term outcomes including allograft loss and death. Methods: 135 renal transplant recipients undergoing 161 contrast-enhanced CT scans (CT) or coronary angiograms (Cath) between years 2000 and 2013 were identified. Contrast agents were iso- or low-osmolar. CIN was defined as a rise in serum creatinine (SCr) by > 0.3 mg/dl or 25% from baseline within 4 days of contrast exposure. After excluding 85 contrast exposures where patients had no SCr within 4 days of contrast administration, 76 exposures (CT: n=45; Cath: n=31) in 50 eligible patients were analyzed. Risk factors assessed included demographics, comorbid conditions, type/volume of contrast agent used, IV fluids, N-acetylcysteine (NAC) administration and calcineurin inhibitor use. Bivariate and multivariable analyses were used to assess the risk of CIN. Results: Incidence of CIN was 13% following both, CT (6 out of 45) and Cath (4 out of 31). Significant bivariate predictors of CIN were IV fluid administration (p = 0.05), lower hemoglobin (p = 0.03) and lower albumin (p = 0.02). In a multivariable model, CIN was predicted by NAC (p = 0.03) and lower hemoglobin (p = 0.01). Calcineurin inhibitor use was not associated with CIN. At last follow up, CIN did not affect allograft or patient survival. Conclusions: CIN is common in kidney transplant recipients, and there is room for quality improvement with regards to careful renal function monitoring post contrast exposure. In our study, NAC exposure and lower hemoglobin were associated with CIN. Calcineurin inhibitor use was not associated with CIN. Our sample size is small however, and larger prospective studies of CIN in renal allografts are needed.